In Situ Structural Restraints from Cross-Linking Mass Spectrometry in Human Mitochondria - Ryl, Petra S J; Bohlke-Schneider, Michael; Lenz, Swantje; Fischer, Lutz; Budzinski, Lisa; Stuiver, Marchel; Mendes, Marta M L; Sinn, Ludwig; O'Reilly, Francis J; Rappsilber, Juri (Journal of proteome research, 2020)
The field of structural biology is increasingly focusing on studying proteins in situ, i.e., in their greater biological context. Cross-linking mass spectrometry (CLMS) is contributing to this effort, typically through the use of mass spectrometry (MS)-cleavable cross-linkers. Here, we apply the popular noncleavable cross-linker disuccinimidyl suberate (DSS) to human mitochondria and identify 5518 distance restraints between protein residues. Each distance restraint on proteins or their interactions provides structural information within mitochondria. Comparing these restraints to protein data bank (PDB)-deposited structures and comparative models reveals novel protein conformations. Our data suggest, among others, substrates and protein flexibility of mitochondrial heat shock proteins. Through this study, we bring forward two central points for the progression of CLMS towards large-scale in situ structural biology: First, clustered conflicts of cross-link data reveal in situ protein conformation states in contrast to error-rich individual conflicts. Second, noncleavable cross-linkers are compatible with proteome-wide studies.